A Binary Particle Swarm Optimization Approach to Optimize assembly sequence planning - Jameel Abdulla, Ahmed Mukred; Zuwairie, Ibrahim, Dr.; Ismail R., Ibrahim; Asrul, Adam; Wan Khairunizam, Wan Ahmad, Dr.; Zulkifli, Md Yusof; Norrima, Mokhtar, Dr. (American Scientific Publishers, 2013)
Link to publisher's homepage at http://www.aspbs.com/